Penerapan Prinsip Tanggung Jawab Perdata Terhadap Perusahaan Angkutan Barang Atas Kecelakaan Truk Over Dimension and Over Loading - Lalita Rahayu, Kinanti; Sutrisno (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Over Dimension and Over Loading trucks have become one of the main factors in the increased risk of traffic accidents in Indonesia. This condition raises issues regarding the form of civil liability of freight transportation companies. This research aims to analyze the civil liability of companies for accidents caused by Over Dimension and Over Loading trucks and forms of legal protection for victims. This research uses a normative method with a statutory approach and conceptual approach, which examines the Civil Code, Law Number 22 of 2009 concerning Road Traffic and Transportation, as well as related legal regulations. Transportation companies can be held civilly liable based on legal liability principles. Legal protection for victims is basically available through compensation lawsuits, although it is often constrained by proof of fault and weak law enforcement. Therefore, this research concludes that strengthening supervision, consistent law enforcement against Over Dimension and Over Loading violations, and consideration of implementing reverse burden of proof are needed to provide more effective legal protection for victims while disciplining transportation companies.